2014
DOI: 10.1177/2150135113507290
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Levels of Tumor Necrosis Factor-α Correlate With Outcomes in Children and Adults With Tetralogy of Fallot Undergoing Corrective Surgery

Abstract: We demonstrated a rise in serum TNF-α levels in patients with TOF undergoing definitive repair on CPB, which correlated with preoperative severity of cyanosis, nutritional status, and adverse clinical outcomes. The TNF-α levels may be monitored to identify cyanotic patients at an increased risk of exhibiting augmented IR to CPB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 34 publications
2
18
0
Order By: Relevance
“…It has been shown that pro‐inflammatory cytokines are present in the myocardium of patients with congenital heart disease and concentrations are higher in patients with tetralogy of Fallot than in those with ventricular septal defects . A recent study demonstrated a rise in serum tumor necrosis factor α (TNF‐α) levels in patients undergoing intracardiac repair for tetralogy of Fallot . The authors attributed such a result to pressure overload of the right ventricle leading to upregulation of TNF‐α or repression of anti‐inflammatory interleukin‐10 by chronic hypoxemia.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that pro‐inflammatory cytokines are present in the myocardium of patients with congenital heart disease and concentrations are higher in patients with tetralogy of Fallot than in those with ventricular septal defects . A recent study demonstrated a rise in serum tumor necrosis factor α (TNF‐α) levels in patients undergoing intracardiac repair for tetralogy of Fallot . The authors attributed such a result to pressure overload of the right ventricle leading to upregulation of TNF‐α or repression of anti‐inflammatory interleukin‐10 by chronic hypoxemia.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 12 studies met our inclusion criteria for this meta‐analysis . These 12 included studies were composed of 190 CHD patients treated with CPB surgery.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 12 studies met our inclusion criteria for this metaanalysis. 21,24,[32][33][34][35][36][37][38][39][40][41] These 12 included studies were composed of 190 CHD patients treated with CPB surgery. The heterogeneity was significantly observed (T1 vs T2: I 2 =92.4%, P h <.001; T2 vs T3:…”
Section: Associations Between the Changes Of Tnfα Serum Levels And mentioning
confidence: 99%
See 2 more Smart Citations